Extensive diversity of branched-RNA-linked multicopy single-stranded DNAs in clinical strains of Escherichia coli. - Sun, J (1989)
Recently it was shown that a clinical strain of Escherichia coli contains a reverse transcriptase that is essential for the synthesis of a branched-RNA-linked multicopy single-stranded DNA (msDNA). We now have examined 113 independent clinical isolates of E. coli for the existence of msDNA and found that 7 strains contained msDNA. Four of them were further analyzed by hybridization analysis, which indicated that three of the msDNAs were different, having little sequence homology. When the reverse transcriptase gene associated with one of these msDNAs was used as a probe, it did not hybridize with chromosomal DNA from the other strains containing msDNA. These results indicate that some clinical E. coli strains carry their own unique msDNA-synthesizing systems; msDNAs produced by these systems have little, if any, sequence homology in their RNA and DNA molecules and the reverse transcriptases required for the production of msDNA also have little sequence similarity. Such extensive diversity of the msDNA-synthesizing systems supports the notion that they were acquired by the E. coli genome late during the evolution of E. coli.